A Pilot Study to Evaluate the Role of Therapeutic Drug Monitoring of Pegfilgrastim in Lymphoma Patients Receiving Chemotherapy. (March 2014) - See, Michelle; Shih, Vivianne Lee Chuen; Ho, Han Kiat; Tang, Tiffany Pooi Ling; Farid, Mohamad; Quek, Richard Hong Hui; Tao, Miriam; Lim, Soon Thye; Chan, Alexandre
Background: Despite primary prophylaxis of febrile neutropenia (FN) with pegfilgrastim, studies have demonstrated a significant number of breakthrough FN events among Asian lymphoma patients receiving chemotherapy. This study was designed to investigate the association of pegfilgrastim concentrations during the lowest point of absolute neutrophil count (ANC nadir) after chemotherapy administration and the occurrence of breakthrough FN, to evaluate whether Therapeutic drug monitoring of pegfilgrastim can guide management of FN. Methods: This was a single-centre, prospective cohort study of Asian lymphoma patients who received prophylactic pegfilgrastim after completion of their chemotherapy. Pegfilgrastim serum concentrations were measured from blood samples taken during ANC nadir and at development of breakthrough FN using an enzyme-linked immunosorbent assay. Descriptive statistics, t-tests and correlation curves were used in the statistical analyses. Results: Nineteen patients were recruited from May to August 2012 and received 21 cycles of pegfilgrastim. Three (15.8%) developed breakthrough FN. The median pegfilgrastim concentration among patients who developed breakthrough FN was 0.257 (0.231–0.631) ng/ml, compared to 0.299 (0.001–0.829) ng/ml in patients who did not (p=0.740). Baseline ANC levels were significantly lower in patients with breakthrough FN (3.59 × 10 9 /L, range 2.71–3.87) versus those who did not (5.36 × 10 9 /L, range 2.80–16.48; p=0.014). Conclusion: There was no difference in pegfilgrastim levels during ANC nadir between patients who developed breakthrough FN and those who did not, but the study was underpowered. Therapeutic drug monitoring of pegfilgrastim cannot be recommended at this time.